P251 Disseminated Histoplasmosis in a Ghanaian HIV Patient: Role of Urine Histoplasma Antigen Testing in Rapid Diagnosis. (20th September 2022) - Agyei, Martin; Ocansey, Bright; Otoo, Benjamin; Ofori, Akua; Norman, Betty; Erskine, Isaac
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Background: The inhalation of the thermally dimorphic fungus Histoplasma capsulatum, may result in a wide spectrum of clinical manifestations, ranging from asymptomatic to acute or chronic pulmonary infection to disseminated infection. Symptomatic infections usually occur with high-level exposures or in immunocompromised patients mainly people with HIV. Despite the improved access to antiretroviral therapy, HIV-associated histoplasmosis remains a significant opportunistic infection in endemic regions including Africa. Unfortunately, histoplasmosis is rarely on the diagnostic radar of clinicians in several African countries such as Ghana due to insufficient awareness, inadequate epidemiological data, and poor fungal diagnostic capacity. Herein, we present a case of disseminated histoplasmosis in an HIV/AIDS patient in a tertiary hospital in Ghana. Case Presentation: Clinical history: A 43-year-old female was referred to the Dermatology Clinic of the Komfo Anokye Teaching Hospital (KATH) with symptoms of fever, cough, and anorexia. She had a history of a skin rash six weeks prior, which initially began on her face and later spread to the trunk and extremities. She was a known HIV/AIDS patient on anti-retroviral drugs (EFV, TFV, 3TC) with no other chronic conditions. She was anemic with a previous hemoglobin level of 7.6 g/dl. Initial diagnostic workup for cutaneous bacterial or viral infection detected no abnormality. Examination: She was semi-conscious, and her nostrils were clogged with crust. The patient appeared pale, warm, and anicteric. The face, trunk, and extremities (including palms) were covered with mucocutaneous erosions, ulcers, multiple papule plaques, and nodules. Examination of the cervix revealed the presence of lymph nodes. Investigations: A fungal diagnostic work-up was done to rule out cutaneous or disseminated mycosis particularly cryptococcosis which was previously captured as a differential diagnosis. Serum cryptococcal antigen lateral flow assay (LFA) (CrAg LFA, IMMY) and Aspergillus galactomannan (GM) (sona Aspergillus GM LFA, IMMY) tests were both negative, but urine Histoplasma GM enzyme immunoassay (EIA) (clarus Histoplasma GM EIA, IMMY) test was positive with a very high optical density indicating high fungal burden was reported. A skin biopsy was also sent for histopathology and fungal culture. Histopathology analysis revealed the presence of yeast cells with round central nuclei and cytoplasmic clearing. Special staining with Periodic acid–Schiff (PAS) confirmed the presence of yeast cells, suggestive of histoplasmosis. Fungal culture was however negative after 8 weeks of incubation. A diagnosis of disseminated histoplasmosis was made. Treatment and outcome: The patient was administered 200 mg bid of itraconazole. Few weeks after treatment, most of her skin lesions and ulcers were healed. The patient was discharged on itraconazole after the disappearance of some of her lesions. Few weeks later, the patient was admitted but died due to complications of anemia. Conclusion: Disseminated histoplasmosis in HIV may be a relatively common but largely unrecognized condition in Ghana. This case report highlights the need to improve awareness of histoplasmosis among clinicians in Ghana and enhance laboratory capacity to provide timely simple contemporary fungal tests for rapid diagnosis and prompt initiation of effective antifungal agents.